Shock response of magnesium single crystals at normal and elevated temperatures - Kanel,GI; Garkushin,GV; Savinykh,AS; Razorenov,SV; de,Resseguier T; Proud,WG; Tyutin,MR (Journal of Applied Physics, 2014)
A series of magnesium single crystals, from 0.2 to 3 mm thick, were shock loaded in directions parallel and perpendicular to the c-axis of the hexagonal closed packed (hcp) structure and at 45° to the c-axis. Shock compression along the c-axis is associated with the largest Hugoniot elastic limit (HEL) for this material. Microscopic observation of recovered c-cut samples demonstrated intense twinning with a greater density of twins near the impact surface. The low-energy basal slip was activated by shock loading along the inclined direction and has the smallest HEL. In all cases, we observe the decay of the elastic precursor wave and growth of the HEL with increasing temperature. For the inclined shock compression after the HEL, two plastic waves were found where the stress level of the first plastic wave depends on the peak shock stress. Finally, the largest spall strength was along the transversal direction and the smallest in the off-axis direction. The fracture surface of the sample of transversal orientation contains numerous groves oriented along the base planes of the crystals.